Clinical Features and Outcome of SARS-CoV-2 Infection in Neonates: A Systematic Review - Dhir, Shashi Kant (J Trop Pediatr, 2020)
OBJECTIVE: The objective of this study is to systematically synthesize the currently available literature on various modes of transmission (congenital, intrapartum, and postpartum), clinical features and outcomes of SARS-CoV-2 infection in neonates. METHODS: We conducted a comprehensive literature search using PubMed, EMBASE, and Web of Science until 9 June 2020. A combination of keywords and MeSH terms, such as COVID-19, coronavirus, SARS-CoV-2, 2019-nCoV, severe acute respiratory syndrome coronavirus 2, neonates, newborn, infant, pregnancy, obstetrics, vertical transmission, maternal–foetal transmission and intrauterine transmission, were used in the search strategy. We included studies reporting neonatal outcomes of SARS-CoV-2 proven pregnancies or neonatal cases diagnosed with SARS-CoV-2 infection. RESULTS: Eighty-six publications (45 case series and 41 case reports) were included in this review. Forty-five case series reported 1992 pregnant women, of which 1125 (56.5%) gave birth to 1141 neonates. A total of 281 (25%) neonates were preterm, and caesarean section (66%) was the preferred mode of delivery. Forty-one case reports describe 43 mother-baby dyads of which 16 were preterm, 9 were low birth weight and 27 were born by caesarean section. Overall, 58 neonates were reported with SARS-CoV-2 infection (4 had a congenital infection), of which 29 (50%) were symptomatic (23 required ICU) with respiratory symptoms being the predominant manifestation (70%). No mortality was reported in SARS-CoV-2-positive neonates. CONCLUSION: The limited low-quality evidence suggests that the risk of SARS-CoV-2 infections in neonates is extremely low. Unlike children, most COVID-positive neonates were symptomatic and required intensive care. Postpartum acquisition was the commonest mode of infection in neonates, although a few cases of congenital infection have also been reported.